2014
DOI: 10.7717/peerj.507
|View full text |Cite|
|
Sign up to set email alerts
|

No population bias to left-hemisphere language in 4-year-olds with language impairment

Abstract: Background. An apparent paradox in the field of neuropsychology is that people with atypical cerebral lateralization do not appear to suffer any cognitive disadvantage, yet atypical cerebral lateralization is more common in children and adults with developmental language disorders. This study was designed to explore possible reasons for this puzzling pattern of results.Methods. We used functional transcranial Doppler ultrasound (fTCD) to assess cerebral blood flow during language production in 57 four-year-old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 74 publications
2
26
0
Order By: Relevance
“…Previous studies comparing typically developed 3-to 5-year-old children to clinical groups suggest left activation in children without language problems. However, findings from this age range also suggest that the reduction or reversal of left-lateralised response to language in clinical groups is not predictive of impairment at an individual level (Bishop et al, 2014). Furthermore, a typical left side activation to phonemic contrasts compared to right side activation to prosodic contrasts (Sato et al, 2011) fits nicely with the proposition by Minagawa-Kawai et al (2011) that newly learned sounds are captured in the left-dominant phonetic and lexical circuits, as opposed to a bilateral activation for syntax, with which prosody heavily interfaces.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Previous studies comparing typically developed 3-to 5-year-old children to clinical groups suggest left activation in children without language problems. However, findings from this age range also suggest that the reduction or reversal of left-lateralised response to language in clinical groups is not predictive of impairment at an individual level (Bishop et al, 2014). Furthermore, a typical left side activation to phonemic contrasts compared to right side activation to prosodic contrasts (Sato et al, 2011) fits nicely with the proposition by Minagawa-Kawai et al (2011) that newly learned sounds are captured in the left-dominant phonetic and lexical circuits, as opposed to a bilateral activation for syntax, with which prosody heavily interfaces.…”
Section: Discussionmentioning
confidence: 71%
“…In combination with studies in older and younger samples, as well as clinical populations of a similar age, the results help complete a developmental picture of the lateralised language response and add weight to the growing opinion that such a response develops very early, but is largely guided by experience and other environmental factors. This helps explain why a predominant left activation in typically developing children compared to reduced left activation seen in many clinical populations does not predict language skill at an individual level (Bishop et al, 2014). The results also highlight a novel predictor of ability, namely the variability in lateralised response during this age, previously shown using fMRI data in older adults (Grady & Garrett, 2014).…”
Section: Resultsmentioning
confidence: 82%
“…In participants with language impairment, a number of studies have reported a higher incidence of atypical laterality or lower laterality indices when compared to control groups (Whitehouse & Bishop, 2008;Illingworth & Bishop, 2009;de Guibert et al, 2011;Badcock et al, 2012;Waldie et al, 2013;Bishop et al, 2014). This has suggested the possibility that atypical lateralisation could constitute an endophenotype for language impairment, mediating the relationship between an original etiological factor such as a genetic predisposition and impaired language function (Bishop, 2013).…”
Section: Language Lateralisation and Language Ability / Impairmentmentioning
confidence: 99%
“…In the light of such findings, the current paper tests an alternative hypothesis raised by Bishop (Bishop, 2013;Bishop et al, 2014) that consistency rather than degree of language lateralisation may constitute an aetiological risk factor for development of language impairment. Genetic accounts have suggested two underlying phenotypes for cerebral lateralisation: one with a left brain bias and one with no bias to left hemisphere language (Annett, 1985;McManus & Bryden, 1992).…”
Section: Atypical Versus Inconsistent Lateralitymentioning
confidence: 88%
“…In participants with language impairment, a number of studies have reported a higher incidence of atypical laterality or lower laterality indices when compared to control groups (Badcock, Bishop, Hardiman, Barry, & Watkins, 2012;Bishop, Holt, Whitehouse, & Groen, 2014;de Guibert et al, 2011;Illingworth & Bishop, 2009;Waldie, Haigh, Badzakova-Trajkov, Buckley, & Kirk, 2013;Whitehouse & Bishop, 2008). This has suggested the possibility that atypical lateralisation could constitute an endophenotype for language impairment, mediating the relationship between an original etiological factor such as a genetic predisposition and impaired language function (Bishop, 2013).…”
Section: Language Lateralisation and Language Ability/impairmentmentioning
confidence: 99%